EFFECT OF DIFFERENT FEED APPLICATION RATE ON GROWTH, SURVIVAL ANDCANNIBALISM OF AFRICAN CATFISH, CLARIAS GARIEPINUS FINGERLINGS - Marimuthu, Kasi; Umah, Ramachandram; Muralikrishnan, Sundararaman; Xavier, Rathinam; Kathiresan, Sathasivam (Emirates Journal of Food and Agriculture, 2011)
In aquaculture feeding rate is an important factor affecting the growth of fish, and thus determining the optimal feeding rate is important to the success of any aquaculture operation. In the present study aimed to investigate the effect of different feeding rate on the growth, survival, cannibalism and body composition of African catfish, Clarias gariepinus fingerlings (initial weight; 1.629± 0.016g). The commercial catfish feed was used and it consists of 38% protein, 5% lipid, 15% ash and 12% moisture. Four feeding rates were evaluated (2%, 5%, 8% and 12%), as a percentage of fish body weight, with three replicates per treatment. The fishes were fed twice per day at 08:30 and 17: 30 hr. At the beginning of the experiment and at 7-day intervals all the fish from each tank were collected, counted, individually measured (nearest mm) and weighed (nearest mg) for four weeks. After each sampling period, the amount of feed given was adjusted according to the biomass in each tank. Final weights were significantly greater (p< 0.05) than initial weights in all the feeding rate. At 8% and 12% feeding rate, C. gariepinus fingerlings were found to achieve maximum growth. The best feed conversion ratio (1.00±0.086) was observed in 8%, followed by (1.250±0.010) in 12% feeding rate. Significantly the highest specific growth rate (6.590±0.100) was obtained in 12% followed by (6.047±0.291) in 8% feeding rate. Fish survival did not increase by providing more feed. Cannibalism was also not reduced by providing commercial feed. The fish fed at 2% feeding rate had the highest ash contents but lowest lipid content, while the fish fed at 12% feeding rate had the highest lipid content than the other feeding rate. Based on the growth performance, feed efficiency data obtained in the present study suggest that the optimum feeding rate of 8% bw/day for African catfish, C. gariepinus fingerlings.